KARAKTER KERBAU DALAM KARYA KERAMIK - FAUZAN ZULDARWAN, Dra. Jupriani, M.Sn., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2018)
Buffalo in general has the characteristics of the color of gray-black skin, short and muscular body, round shape, wide chest circumference, short legs and straight, and horns are wide and curved. With such a buffalo body shape seemed creepy. The author's interest in buffalo and the importance of the buffalo role for life inspired writers to make it into a work of ceramic art. The method of creating this work is made through several stages. Sketches are made manually with buffalo animals as the main object, the material used is red clay as the main material of making works, then paint the poster as a coloring material Karya. Buffalo in some movements made with printing and massage techniques. Seven of the resulting works are given the title of each of the movement of eating, standing, pulling plow movements, wallowing, sleeping while mengunya food, sleeping while soaking, blocking.Keywords: Buffalo and ceramics.